Współpraca firm badawczych z ośrodkami naukowymi - ocena wykorzystania metod ilościowych w praktyce badawczej - Perek-Białas, Jolanta (Co Operation of Research Companies with Research Educational Establishments - Estimation of Quantitative Methods Usage in Research Practice, 2006)
Based on interviews conducted in 15 marketing and public opinion research companies in Poland and on one visit in such a company in Germany, it could be said that there is a will of co-operation of those firms with research educational establishments, mostly concerning market research developments. This could be observed not only due to sharing views and experience in using quantitative methods in practice of market research but as well as in showing the recent changes between clients and research companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 486-495